Employee retention in anti money laundering department of selected banks in Kuala Lumpur - Kagaithri, Palani (2021)
This research was conducted to determine the factors influencing employee retention in Anti-Money Laundering Department (AML) of selected banks in Kuala Lumpur. This research adopts quantitative method to identify the relationship between independent variables which is flexible work arrangement, family leave system, recreational services, and employee assistant program to dependent variable employee retention. Electronic questionnaires were distributed to employees in Anti-Money Laundering Department (AML) of three selected banks and 143 responses were received for analysis. The questionnaire consists of 43 items using the five-point Likert scale. Each hypothesis was tested using Statistics Package for Social Science (SPSS) version 25.0. The obtained data were analyzed using descriptive and inferential analysis namely correlation and regression analysis. Five hypotheses were formed to perform the inferential analysis to determine the relationship between independent variables and dependent variables. The results of the study showed that all four factors which is flexible work arrangement, family leave systems, recreational services and employee assistant program is positively related to employee retention. It was identified that family leave systems and employee assistant program are the main contributor towards employee retention in AML Department in the selected banks. Respondents’ demographic details was also discussed using percentage and frequencies. Various recommendations for further research were also addressed.